Pharmacoeconomic analysis of netakimab in the treatment of ankylosing spondylitis: perspective of Russian healthcare system - A. V. Rudakova; I. Z. Gaydukova (Фармакоэкономика, 2025)
Objective: to evaluate clinical and economic effectiveness of netakimab therapy for ankylosing spondylitis (AS) in comparison with other biological disease-modifying antirheumatic drugs (bDMARDs) currently employed in clinical practice in the Russian Federation.Material and methods. The evaluation of clinical and economic effectiveness was carried out from the perspective of the healthcare system based on the results of a network meta-analysis of randomized clinical trials. Clinical effectiveness criteria included indicators of therapeutic response according to the Assessment of Spondyloarthritis International Society criteria, specifically ASAS20 and ASAS40, as well as by the Bath Ankylosing Spondylitis Disease Activity Index BASDAI50. A time horizon of the study was set at 2 years. Costs of pharmaceuticals were calculated according to the registered maximum retail prices, inclusive of value-added tax. In case of availability of biosimilars on the market, calculations were based on the minimum values of the registered prices.Results. According to the network meta-analysis, the efficacy of netakimab significantly surpassed that of other bDMARDs or demonstrated a trend towards higher efficacy for AS. The costs per patient achieving an additional response compared to standard therapy without bDMARDs when treated with netakimab appeared 31–77%, 34–80%, and 20–69% lower than those of other bDMARDs, according to ASAS20, ASAS40, and BASDAI50 criteria, respectively.Conclusion. Netakimab exhibits a higher clinical and economic effectiveness compared to other bDMARDs and may be considered as the preferred therapeutic option in comparable clinical scenarios for active AS, thereby ensuring cost-effectiveness for the healthcare system along with achieving the efficacy criteria compared to the standard treatment regimen. The limitations of the analysis determine the need for further research in this area.